Digital Ulcers as Presentation of Carpal Tunnel Syndrome - Gomes, T. F. (2020)
Ulcerating and mutilating variant of carpal tunnel syndrome occurs in longstanding cases of untreated disease. Pa- tients present with painless ulcers of the second and third fingers, accompanied with other cutaneous and sensory changes. These patients are often misdiagnosed as having a Raynaud disease or systemic sclerosis. Clinical assessment is the gold standard for the diagnosis of carpal tunnel syndrome, but hand radiography and electromyography help supporting the diagnosis. The authors present two cases of this ulcerating variant of carpal tunnel syndrome.